Використання лізингу – перспективний шлях розвитку вугледобувної промисловості - Мєшкова, В.С. (Економіка промисловості, 2012)
Розглянуто сутність лізингу та можливість використання лізингу у вугільній промисловості. Проаналізовано необхідність становлення і розвитку лізингу для технічного переозброєння підприємств вугільної промисловості. Доведено, що лізинг є ефективним інструментом оновлення основних фондів та збільшення виробничих потужностей підприємств та при сучасній економічній ситуації може сприяти мобілізації коштів для інноваційного розвитку вугільної галузі. Ключові слова: лізинг, вугільна промисловість, розвиток, основні фонди, технічне пере¬озбро¬єння. Рассмотрены сущность лизинга и возможность использования лизинга в угольной промышленности. Проанализированы необходимость становления и развития лизинга для технического перевооружения предприятий угольной промышленности. Доказано, что лизинг является эффективным инструментом обновления основных фондов и увеличения производственных мощностей предприятий и при современной экономической ситуации может способствовать мобилизации денежных средств для инновационного развития угольной отрасли. Ключевые слова: лизинг, угольная промышленность, развитие, основные фонды, техническое перевооружение. The coal industry is one of the most important parts of the economics of Ukraine, which manufactures products that are necessary for energy and metallurgical sectors of the economics and for providing of energy security of the country. However, the technical condition of the major part of coal-mining enterprises is rather unsatisfactory. A promising method of providing for equipment modernization is renting, one form of which is leasing. The purpose of the article is proving the urgency of development of leasing in the coal field of Ukraine, enterprises of which have lack of funds for getting modern mining equipment. Technical modernization of mines is held over because of the deficit of investment resources. The country is not able to support the investment transformation of the field in the full amount. It impels the coal field to make a non-traditional decision which makes it possible to carry out technical modernization of the coal field by mobilization of assets of entrepreneurial structures when state investments are low. The nature of leasing, and possibility of leasing usage in the coal industry were observed. The necessity of formation and development of leasing for technical modernization of coal industry enterprises was analysed. The urgency of leasing development in Ukraine is conditioned by an unfavourable condition of equipment parking: significant specific weight of obsolescent equipment, low efficiency of its usage, absence of spares. The main advantages of leasing are the amount of payments that are fixed for a long period, possibility of full financing of production groups, liquidity of capital investments, and creating of working places. Moreover, leasing can help to settle the quiet sharp problem for coal enterprises of timely promotion of innovative facilities and resources concentration. The favourable conditions for development of leasing relationships in Ukraine were formed. The preconditions for that are: great necessity in renovation of production facilities, non-payment crisis, aggravation of production distribution, slowdown in production, etc. Leasing gives a possibility to not involve loan capital and not freeze the own capital, but to save on expanses that relate to property ownership, and to make use of tax remissions and faster amortization of leasing object. Thus for development of the coal field it is necessary to apply new technologies of mining in refining coalfaces, progressive schemes of development of coal beds, the most effective schemes of preparation of a mine field. Because of lack of funds leasing can be a promising method. Because of its specific economic nature, leasing type of activity is able to make a great contribution to raising and developing the national economics, and as for the international level - to create and to consolidate new relations with foreign investors. It is proved that leasing is an effective instrument for renovation of the fixed assets and for growth of production facilities of enterprises, and that it can promote mobilization of monetary funds for innovative development of the coal field in the modern economic conditions. Keywords: leasing, coal industry, develop-ment, fixed assets, technical modernization.